PENGUKURAN TOTAL DISSOLVED SOLID (TDS) DALAM FITOREMEDIASI DETERJEN DENGAN TUMBUHAN Sagittaria lancifolia - Elisa Kustiyaningsih; Rony Irawanto (Jurnal Tanah dan Sumberdaya Lahan, 2020)
As the population increases, the need for detergent will increase. This study aimed to determine the value of TDS in detergent solution at different concentrations and detention times. This study was an experimental study using a randomized block design with three treatment factors. The treatments included phytoremediation (presence or absence of plants), detergent concentrations used were 10, 50, and 75 ppm, and detention times were 7 and 14 days, each with three replications. The tool used was the TDS Meter. The data obtained in the form of TDS values were further analyzed descriptively and presented in the form of tables, graphs and descriptive analysis. The results showed that the TDS values fluctuated every day. The lowest average TDS value was found in phytoremediation treatment with a concentration of 10 ppm with a detention time of 7 days which was 174 mg L-1, while the highest average TDS value was found in phytoremediation treatment with a concentration of 75 ppm with a detention time of 14 mg of 237 mg L-1. The higher the concentration of detergent and the longer the detention time in the phytoremediation treatment, the higher the average TDS value.